The Effect of E-Serviceescape in Increasing Customer Loyalty through Customer Satisfaction and Trust as Intervening Variables on Tokopedia Users in Malang - Fahrul Ulum; M. Ridwan Basalamah; Eka Farida (Budapest International Research and Critics University, 2022)
The development of e-commerce in Indonesia has made the competition for e-commerce players even tighter. Thus, customer loyalty is an important factor for the company. Tokopedia is one of the online marketplaces in Indonesia. Along with the number of e-commerce companies in Indonesia, one way that can be done to be able to compete is through increasing e-service escape on the website marketplace. E-Servicescape are all elements on the website that are used by companies to deliver digital services to consumers. The purpose of this study was to determine the effect of e-serviceescape in increasing customer loyalty through customer satisfaction and trust as intervening variables for Tokopedia users in the city of Malang. This type of research is explanatory research with a quantitative approach. The variables in this study are e-serviceescape, customer satisfaction, trust and customer loyalty. The population in this study were Tokopedia users in the city of Malang. The sample in this study amounted to 90 respondents who were taken by purposive sampling technique. The analytical technique used is descriptive analysis technique and inferential analysis using SmartPLS. The results showed that e-serviceescape had a significant effect on customer satisfaction, customer trust and loyalty, customer satisfaction and trust had a significant effect on customer loyalty, e-serviceescape had a significant effect on customer loyalty through customer satisfaction and trust as intervening variables.